MATERNAL C-REACTIVE PROTEIN IN PREGNANCY AND ITS RELATION WITH EARLY ONSET NEONATAL SEPSIS - Zahid, Muhammad; Zaman, Saeed; Shahzad, Sohail; Shah, Sajid Ali; Javed, Sana; Khan, Ammara Mushtaq (Pakistan Armed Forces Medical Journal, 2021)
Objective:To determine association of early-onset neonatal sepsis (EONS) in newborns of serum C-reactive protein positive mothers.Study Design:  Cross sectional studyPlace and duration of study:  Department of Pediatrics, Combined Military Hospital Quetta, Pakistan from September 2016 to March 2018.Material and Methods: 105 neonates (both gender) of all mothers who were C - reactive protein positive were enrolled in this study using inclusion and exclusion criteria.Neonatal sepsis was diagnosed by clinical examination, which was carried out by senior pediatrician, blood complete picture and c reactive protein. Neonates were treated as per departmental protocol. Stratification was done in regard to gestational age, birth weight and age of neonates in hours. Post stratification chi square test was applied and p-value less than 0.05 was considered significant.Results:Out of total 105 patients, 46 (44%) were male and 59 (56%)were female neonates. Amongst the babies of 105 CRP positive mothers, 79 babies were having signs and symptoms of neonatal sepsis and 26 babies were having no signs and symptoms of neonatal sepsis with statistically significant relation between maternal CRP and neonatal sepsis of p value